2017
DOI: 10.1002/app.45281
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between structure and properties in high‐performance PA6/SEBSgMA/(PPO/PS) blends: The role of PPO and PS

Abstract: This work aimed at studying the role of poly(phenylene oxide) (PPO) and polystyrene (PS) in toughening polyamide‐6 (PA6)/styrene‐ethylene‐butadiene‐styrene block copolymer grafted with maleic anhydride (SEBS‐g‐MA) blends. The effects of weight ratio and content of PPO/PS on the morphology and mechanical behaviors of PA6/SEBS‐g‐MA/(PPO/PS) blends were studied by scanning electron microscope and mechanical tests. Driving by the interfacial tension and the spreading coefficient, the “core–shell” particles formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Similar results have also been reported in other research. 28,29 On the other hand, too strong interfacial adhesion may prevent the interfacial debonding process which plays an important role in many toughening systems. 30 For instance, Sue et al reported that for polycarbonate/polyethylene (PC/PE) blends, debonding at the interface was the major toughening mechanism, which released triaxial stress around microvoids and caused matrix shear yielding.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Similar results have also been reported in other research. 28,29 On the other hand, too strong interfacial adhesion may prevent the interfacial debonding process which plays an important role in many toughening systems. 30 For instance, Sue et al reported that for polycarbonate/polyethylene (PC/PE) blends, debonding at the interface was the major toughening mechanism, which released triaxial stress around microvoids and caused matrix shear yielding.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[19,20] Therefore, the entanglement density of the PPO/PS matrix could be controlled by adjusting the content of PPO in the matrix, thus improving the toughening ability of the matrix. [21][22][23][24] It was found that rubber polymers containing styrene (St) units, such as high-impact polystyrene (HIPS), could improve the impact properties of the PPO/PS alloy. [25,26] Although HIPS could ensure the good processability of PPO and improve the impact toughness to a certain extent, its toughening efficiency was relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well‐established that there is a close relationship between the phase morphology and final properties of polymer blends. Accordingly, control of the factors affecting the morphology is an essential factor to achieve the desired properties …”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, control of the factors affecting the morphology is an essential factor to achieve the desired properties. [6,7] Incorporation of nanoparticles into the polymer blends has been the subject of a great number of researches in academia and industry. This approach is associated with interesting results such as improving the mechanical properties, adding new characteristics, such as electrical properties, or controlling of the phase morphology.…”
Section: Introductionmentioning
confidence: 99%